Biology and Management of Ragweed Parthenium (Parthenium hysterophorous L.) in Tomato, Pepper, Cucurbit, and Strawberry Production - Nathan S. Boyd; Shaun M. Sharpe; Chris Marble; Shawn Steed (EDIS)
Ragweed parthenium is an herbaceous annual or short-lived perennial weed. It is difficult to manage in many fields due to known resistance to commonly used herbicides. There are a limited number of modes of action that can be used in some vegetable and berry crops. This new 4-page publication of the UF/IFAS Environmental Horticulture Department provides management recommendations. Written by Nathan S. Boyd, Shaun M. Sharpe, Chris Marble, and Shawn Steed. https://edis.ifas.ufl.edu/ep613